Perioperative Management of Flecainide: A Problem-Based Learning Discussion. Issue 4 (April 2021) - Acker, Leah; Bova Campbell, Kristen; Naglee, Colleen; Taicher, Brad; Bronshteyn, Yuriy S.
Abstract : Flecainide is a first-line antiarrhythmic drug used to treat atrial arrhythmias and/or supraventricular tachycardia in those without coronary artery disease or structural heart disease. Even though it is an older antiarrhythmic, flecainide accounted for 1.6 million prescriptions in the United States in 2016, and its utilization is generally increasing. Despite its popularity, flecainide may predispose patients to rapid atrial flutter with resultant hemodynamic compromise, particularly in the physiologically stressful perioperative period. This article reviews the pharmacology of flecainide, describes problematic arrhythmias that may arise specifically during flecainide use, and offers recommendations for perioperative flecainide management.